Brief Normothermic Machine Perfusion Rejuvenates Discarded Human Kidneys. Issue 11 (November 2019) - Hameed, Ahmer M.; Lu, David B.; Patrick, Ellis; Xu, Bo; Hu, Min; Chew, Yi Vee; Keung, Karen; P'ng, Chow H.; Gaspi, Renan; Zhang, Chris; Robertson, Paul; Alexander, Stephen; et al.
Abstract : Background: Normothermic machine perfusion (NMP) may allow resuscitation and improved assessment of kidneys before transplantation. Using discarded human kidneys, we investigated the mechanistic basis and translational potential of NMP compared with cold static storage (CS). Methods: Discarded deceased donor kidneys (n = 15) underwent 1-hour NMP following CS. Renal perfusion, biochemical, and histologic parameters were recorded. NMP was directly compared with CS in paired donor kidneys using simulated transplantation with allogeneic whole blood, followed by assessment of the aforementioned parameters, in addition to RNA sequencing. Results: Kidneys were successfully perfused, with improved renal blood flows and resistance over the course of perfusion, and evidence of urine output (median 21 mL), in all but one kidney. NMP completely resolved nonperfused regions in discarded donation after circulatory death kidneys. In paired kidneys (n = 4 pairs), transcriptomic analyses showed induction of stress and inflammatory pathways in NMP kidneys, with upregulation of pathways promoting cell survival and proliferation. Furthermore, the NMP pairs had significantly better renal perfusion (1.5–2 fold improvement) and functional parameters, and amelioration of cell death, oxidative stress, and complement activation. Conclusions: In this pilot preclinical study using simulated transplantation of paired kidneys, NMP of discarded marginal kidneys demonstrated some significant mechanistic benefits in comparison to CS alone. NMP may have potential to reduce organ discards and enhance early graft function in such kidneys. Abstract : Supplemental Digital Content is available in the text.